Performance Optimization Through Belief System, Boundary Control System, Diagnostic Control, and Interactive Control System - Nazaruddin Ietje; Karuniawati Syolichah Dwi; Yani Indah (SHS Web of Conferences)
This study examines the effect of belief systems, boundary control systems, diagnostic control, and interactive control systems on performance. The permanent employees of the Regional Apparatus Organization in Ngawi Regency were the object and subject of this research. The study employed purposive sampling for its sampling. Primary data were collected by distributing questionnaires to 150 respondents. This study utilized SEM-PLS with SmartPLS v.4.0 software to test the data. Based on the findings, three hypotheses could be tested: diagnostic control had a longterm effect on performance, whereas belief systems, boundary control systems, and interactive control systems did not. Furthermore, by utilizing variables, the belief system, boundary control system, and interactive control system would positively impact performance. Consequently, the trust system, boundary control system, and interactive control system could enhance employee performance in Regional Apparatus Organizations.